Peran Akuntan Berbasis Values Driven Accounting Sebagai Upaya Penciptaan Daya Saing Berkelanjutan - Siti Amerieska (Jurnal Akuntansi, 2017)
Perception  and  focus  in  accounting  is  need  for  a  paradigm  transform  in  thecome at economic turbulence (the uncertainty of business conditions). Accountant rolenot just as a driver compliance, which has the task of preparing the financial statementonly,  but  can  provide  added  value  driven  as  business  partner.Become  business  partnerthe  accountant  should  have  ability  to  making  decision  about  performance,profit  andstrategic  decision.This  study  aims  to  provide  ideas  and  strategic  thinking  to  theaccountant  to  be  more  involved  in  the  role  of  value  driven.  Type  in  this  research  is  adescriptive  study.  Discussion  of  this  article  about  building  paradigm  as  value  driven,how  to  change  the  focus  be  performance,  change  the  paradigm  of  technical  cost  intostrategic level in the corridors of cost management strategy. In addition to value drivenparadigm  that  was  built  in  thisarticle  also  discussed  the  role  of  accountant  strategicmapping to face the uncertainities of business condition.